Brasília”s Historic Urban Landscape : the Paranoá Park Condominium”s case - Priester, Mariana Freitas (2022)
In this paper we will explore the implementation of Paranoá Park Condominium (2014), located on the edge of Paranoá basin, used by the National Historical and Artistic Heritage Institute (IPHAN) as boundary for the surroundings of Urban Ensemble, classified as World Heritage site by UNESCO (1987). To advance toward new approaches as the Historic Urban Landscape (HUL), we will seek to explore the different layers that compose this landscape. It is noted that are still difficulties in the management of urban landscape in Brasília, mainly due to lack of dialogue and understanding between managers and key stakeholders in urban preservation and development of the city. In addition, the notion of urban heritage preservation persists as an isolated discipline among experts in the field.